Um estudo sobre o estabelecimento do controle e da generalização da audiência sobre o comportamento verbal - Pasquinelli, Renata de Souza Huallem (2007)
The present study s goals were to verify (1) the control of distinct audiences over the theme of spoken verbal behavior; (2) the generalization of audience control to new audiences, with distinct physical features; (3) how much direct reinforcement of a given repertoire was necessary for a new audience to assume evocative control over the repertoire; (4) how much direct reinforcement was necessary in the presence of a new audience, to establish the control of this new audience over a second repertoire. Six children, ranging from 4 to 8 years participated in the study. Four puppets, 2 of them humanlike were established as audiences during the experiment. On each condition 2 puppets with distinct features asked each participant to describe 5s films. Each film portrayed a person or child engaged in some action. On the first 3 experimental conditions the first pair of puppets trained and/or tested the emergence of 2 verbal repertoires descriptive of the films: a mentalist/ internalist repertoire composed of descriptions of supposed emotions or purposes (m repertoire) and a externalist repertoire with descriptions of actions or physical characteristics (p repertoire). On the last conditions a second pair of puppets was used to test if direct reinforcement of some responses belonging to one of the repertoires would evoke the same repertoire on new trials with new films. Tests of the effects of a reversal condition with new audiences were also conducted. Results showed (1) the establishment of the puppets as audiences controlling different thematic repertoires; (2) the occurrence of generalization of this evocative function to a new audience after the direct reinforcement of a few responses; (3) the reversal of repertoires evoked by an audience after the reinforcement of a few responses belonging to this repertoire; (4) the emergence of variability on the verbal repertoire of the participants during tests. The role of the audience as discriminative and conditional stimuli and the variability of the verbal responses are discussed